2023
DOI: 10.7759/cureus.33484
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Glucagon-Like Peptide 1 (GLP-1) Receptor Agonists and Sodium-Glucose Cotransporter 2 (SGLT-2) Inhibitors in Decreasing the Occurrence of Adverse Cardiorenal Events in Patients With Type 2 Diabetes

Abstract: Diabetes mellitus is a metabolic disorder characterized by increased serum glucose due to errors in insulin production or response. The prevalence of diabetes mellitus has continued to rise globally over the years, with roughly 7079 persons per 100,000 expected to be impacted by 2030. A vast number of patients with diabetes mellitus experience unfavorable side effects such as weight gain, hypoglycemia, and hepatorenal toxicity from the several diabetic medications available. These adverse effects may result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The administration of empagliflozin can effectively reduce blood glucose levels, safeguard cardiovascular health, enhance cardiac outcomes, promote weight loss, preserve kidney function, and potentially exhibit anti-cancer properties [1,3,[6][7][8][9].…”
Section: The Pharmacological Effects Of Empagliflozinmentioning
confidence: 99%
See 4 more Smart Citations
“…The administration of empagliflozin can effectively reduce blood glucose levels, safeguard cardiovascular health, enhance cardiac outcomes, promote weight loss, preserve kidney function, and potentially exhibit anti-cancer properties [1,3,[6][7][8][9].…”
Section: The Pharmacological Effects Of Empagliflozinmentioning
confidence: 99%
“…SGLT-2 is primarily responsible for facilitating glucose absorption from the distal tubule of the renal system. By impeding the activity of SGLT-2, empagliflozin effectively curtails glucose absorption, resulting in a subsequent decrease in the level of glucose in the blood [1,6,7]. Research has demonstrated that after 52 weeks of treatment with empagliflozin in a group of 127 individuals, the level of glycosylated hemoglobin decreased by 0.57% [2].…”
Section: Reduces Blood Glucose Concentrationsmentioning
confidence: 99%
See 3 more Smart Citations